Ratification of Political Party Management by The Ministry of Law and Human Rights of The Republic of Indonesia (Analysis of The Authority of The Minister of Law and Human Rights in Legalizing The Management of Political Parties): - Munir, Misbahul; Chandra, Anna Erliyana (LPPM Universitas Lampung, 2022)
Drama over the leadership of political parties is common in Indonesia. Most recently, the drama hit the body of the Democrat Party (Indonesia: Partai Demokrat). Some cadres of the